The Specificity of the Polish Reception of Leo Tolstoy in the Light of the Dichotomy “Russia vs. Europe” (Based on Articles Published on the Occasion of the 1908 Anniversary) - Piotrowska, Joanna (Slověne, 2019)
The purpose of this article is to identify and examine the main components of Leo Tolstoy’s image (as an artist, an apostle, and as a philosopher) in the Polish-language press of Austria-Hungary and the Tsardom of Poland in the context of the celebrations to mark the author’s eightieth birthday. I draw upon three contemporary journalistic reactions: an article by Henryk Sienkiewicz in the Kraków newspaper “Czas” (Time), an anonymous piece in the Warsaw daily “Przegląd Poranny” (Morning Review), and another anonymous piece featured in “Kurier Warszawski” (Warsaw Courier). Sienkiewicz’s article represents Tolstoy as a religious preacher and as a writer alien to European culture. In describing the national specificity of Tolstoy the artist, Sienkiewicz departs from the contraposition between backward, non-liberal and unenlightened Russia whose voice is Tolstoy and progressive, liberal and enlightened Europe with which the Polish writer associates himself. Tolstoy is painted in similar colours in the “Kurier Warszawski” feature. However, the anonymous author describes Tolstoy not as a preacher but rather as an original Russian philosopher. “Przegląd Poranny” presents an entirely opposite image of Tolstoy. Here, Tolstoy emerges as a globally significant artist and thinker, whose work is a legacy of international cultural achievement. Polish responses to Tolstoy’s eightieth birthday thus made use of the dichotomy “Russia vs. Europe” in varying degrees. The specificity of Tolstoy’s reception by Polish-language media correlates with the pro-European and pro-Russian positions of the Polish intelligentsia at the time.